Demographic Trends of Sick Leave Absenteeism Among Civil Service Employees at a Federal Agency From 2004 to 2012. Issue 3 (March 2015) - Gajewski, Kim; Burris, Dara; Spears, D. Ross; Sullivan, Kevin; Oyinloye, Oluremi; McNeil, Carrie; Meechan, Paul; Warnock, Eli; Trapp, Jonathan; Decker, K.C.; Chapman, Sandy
Abstract : Objective: To investigate the associations between demographic variables and sick leave use. Methods: We analyzed sick leave use among civil servants at a federal agency (FA) from 2004 to 2012 by demographic and FA-specific variables. We used a mixed methods approach and type III analysis to build a descriptive model of sick leave proportions and demographic variables. Results: Sick absenteeism usage varied significantly (variation of greater than one sick day per year) by sex, Emergency Operations Center response tier, length of service at the FA, age, and general schedule pay grade level. Our final descriptive model contained age, sex, response tier and an interaction term between age and sex. Conclusions: Future studies should examine these associations on smaller time scales, perhaps breaking the data down by month or day of the week.